GUSTATION STUDY IN THE PERIOD OF PATIENTS' ADAPTATION TO REMOVABLE LAMINAR DENTURES - V.Yu. Davydenko (Ukrainian Medical Stomatological Academy, 2016)
Introduction. Worsening of gustatory perception and decrease of the ability to identify and distinguish the main tastes deprives the individual of food pleasure and reduces quality of life. While growing older many people experience deterioration of gustatory perception, leading to severe consequences, resulted in loss of appetite, malnutrition, causing the exacerbation of chronic diseases, the occurrence of new pathology due to depletion of vitamins, proteins, carbohydrates. A number of factors, such as smoking, harmful production conditions and the effect of toxic substances, as well as drugs, narcotic and psychotropic substances, the presence of fillings or dentures in the oral cavity can significantly affect the gustation threshold. Currently, the main group of materials for removable dentures manufacturing is made up by the polymers, i.e., acrylic resins, the process of polymerization of which is run according to free-radical mechanism with the formation of the primary free radicals from the monomer molecules, which further polymerization. The main toxigenic factor of acrylic resins is a monomer, especially its part that is not undergone the reaction of polymerization and is called the "residual monomer". Many studies have been made on negative effect of the monomer on the tissues of prosthetic bed. It has been proved by evidence that the residual monomer, even in small quantities, reduces the activity of the lysozyme in the oral fluid, causing the blastomatous growth of the epithelium. The manufacturing technology, the quality of the material itself and the monomer/polymer ratio affect the level of the residual monomer in dentures. The purpose if the study was the analysis of the extension of changes in gustatory perception in edentulous patients before and after dental prosthetics according to subjective evidence and study of gustation threshold during the adaptation to dentures. Results and Discussion. The paper presents the results of the study of the extension of changes in gustatory perception in edentulous patients before and after dental prosthetics according to subjective evidence and study of gustation threshold during the adaptation to dentures. Many edentulous patients after denture attachment have had complaints as for the deterioration or even loss of taste, they were experiencing in the early period of use of the removable dentures. The analysis of the publications has showed that the problem of gestation recovery in patients during the period of adaptation to full dentures, the effect of residual monomer on the state of gustatory perception has not been fully elucidated. The analysis of 153 questionnaires of the surveyed patients has found that all patients have experienced deterioration of gustatory perception after the complete loss of teeth, while 74,5% of patients have pointed to the worsening of gustation, and 25% have noted the complete loss of taste. 99 (64,6%) of the 153 patients have pointed to the deterioration of the perception of sour and salty; 57 (37,2%) patients have reported about worsening of perception of sweet. Almost all the patients have experienced no change in perception of bitter after tooth loss. The studies have found the worsening of gustatory perception in the first month of using the full dentures in almost of 95% of patients. The significant growth of gustation threshold on the average of 50% has been observed from 7 to 21 days after denture remove. The greatest worsening has been observed in patients' gustatory perception of sour and salty.